Discours numériques et degrés de viralité : caractéristiques linguistiques et traits (techno)discursifs - Claudia Cagninelli (MediAzioni)
This paper focuses on the circulation of digital discourses and their virality in relation to the influence of the technological environment and its affordances. The aim is to identify linguistic and (techno)discursive features that correspond to different degrees of discourse virality. The study is carried out on a thematic corpus of tweets, distinguishing four main levels of discourse virality. Adopting a discursive approach, this study analyzes the linguistic and discursive features that are typical of each level and that could influence the potential dimension of discourse virality.